Translation of the speech act in Quran discourse according to the theory of speech acts : analytical and comparative study of three translations - MEROUANI, Adberrahmane (Journal of Human Sciences, 2020)
The Quranic discourse is miraculous both in its style and demonstration. It is appropriate for all times and places. For these reasons, translators found difficulties to convey its meanings to other languages. The speech acts is one among the linguistic phenomena that brought their attention. The combination of modern approaches and traditional linguistic views may contribute to the addition of new insights to analyze the Quranic discourse, to understand its meaning and to translation It. We chose as corpus "verses of the Quran" from El-Bakara (The cow) chapter, and we are relied on three famous translation. These translations are analyzed and compared to what is said in the Quran interpretation books.